IMPLEMENTASI MANAJEMEN KEPEMIMPINAN DALAM PENCAPAIAN TUJUAN ORGANISASI - Rahmi Aulia; Bambang Kurniawan; Muhamad Subhan (Pusat Riset dan Inovasi Nasional, 2024)
In the current era of globalization, leadership management is very important in an organization. Leadership management is a science that teaches how someone carries out leadership by using all the resources they have and always prioritizing a concept and rules that apply in management science. In carrying out leadership management in an organization it is required to have leadership that has strong leadership character and can carry out the principles of leadership in carrying out its duties in an organization with good leadership management so that organizational goals will be achieved even better.